Al-ghuluwu fi al-amsal al-arabiy of postproverbials in modem arabic literature and perceptive transformations in afro-arab culture (2019)
Al-Ghuluwufi al-amsal al-arabiy (Postproverbial) is a new trend in modem Arabic studies. It is a way to gain the perceptions of learners of the language into Afro-Arabic and Yomba cultures in contemporary times. Through the learning of the subject matter, University of Ibadan students of Arabic Language and Literature explore how much common philosophy is shared between postproverbial expressions in Arabic and Yoruba languages. Afro-Arabic postproverbial demonstrates the trends of modernity within the culture. It absorbs and transforms wisdom accumulated over the few years with the experience of students in their various localities. This paper investigates the exposure to postproverbiality in Arabic among the students of Arabic language and literature who are predominantly Yoruba in the University of Ibadan and how the practice of postproverbials transforms their perceptions and values of Yoruba and Afro- Arab cultural concepts. Thus, two questions are raised: to what extent does the use of postproverbials in the Arabic literature course in the University of Ibadan shed light on Yoruba cultural aspects not regularly covered in Arabic Proverbs? How does the use of postproverbials in the Arabic literature course promote a new understanding among the students and make them discover and reassess their values and preferences in the modem time? The theoretical framework of the paper is adopted from A. Raji-Oyelade’s “Postproverbials in Yomba Culture: A Playful Blasphemy”. The result of this study indicates that students employed their basic knowledge of Arabic language, coupled with their Yomba cultural background, to re-create a number of postproverbial texts within the context of Arabic culture. It also exhibits their level of consciousness in the modem times.